Requalificação do Mercado Central de Macapá - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2017)
This paper aims to draw up a rehabilitation project for Macapá Central Market to give a new function to it without losing their identity. The method used for this will be the case study to obtain user information so as to find out the existing problems on site, from that to the results obtained in qualitative research, develop a project with concepts based on architectural styles of markets They follow the same line of work and also think about the state of the economy and its limitations aiming an architecture that enhances its characteristics and that causes the market to communicate with the environment, seek to maintain their facade for example that are the outstanding identities. It is expected that with this population pass to see the market as an environment that contributes not only to the local economy, but also for culture and leisure of the population.
Keywords: Mercados populares; Cartas patrimoniais; Restauro patrimonial; Mercados públicos; CNPQ::CIENCIAS SOCIAIS APLICADAS